Recent advances in arterial spin labeling perfusion MRI in patients with vascular cognitive impairment - Huang, Dan; Guo, Yunlu; Guan, Xiaoyu; Pan, Lijun; Zhu, Ziyu; Chen, Zeng’ai; Dijkhuizen, Rick M; Duering, Marco; Yu, Fang; Boltze, Johannes; Li, Peiying (Journal of cerebral blood flow and metabolism, 2023)
Cognitive impairment (CI) is a major health concern in aging populations. It impairs patients’ independent life and may progress to dementia. Vascular cognitive impairment (VCI) encompasses all cerebrovascular pathologies that contribute to cognitive impairment (CI). Moreover, the majority of CI subtypes involve various aspects of vascular dysfunction. Recent research highlights the critical role of reduced cerebral blood flow (CBF) in the progress of VCI, and the detection of altered CBF may help to detect or even predict the onset of VCI. Arterial spin labeling (ASL) is a non-invasive, non-ionizing perfusion MRI technique for assessing CBF qualitatively and quantitatively. Recent methodological advances enabling improved signal-to-noise ratio (SNR) and data acquisition have led to an increase in the use of ASL to assess CBF in VCI patients. Combined with other imaging modalities and biomarkers, ASL has great potential for identifying early VCI and guiding prediction and prevention strategies. This review focuses on recent advances in ASL-based perfusion MRI for identifying patients at high risk of VCI.